2016
DOI: 10.1158/1078-0432.ccr-15-2910
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3G Expression Correlates with T-Cell Infiltration and Improved Clinical Outcomes in High-grade Serous Ovarian Carcinoma

Abstract: Purpose APOBEC3 DNA cytosine deaminase family members normally defend against viruses and transposons. However, deregulated APOBEC3 activity causes mutations in cancer. Due to broad expression profiles and varying mixtures of normal and cancer cells in tumors, including immune cell infiltration, it is difficult to determine where different APOBEC3s are expressed. Here, we ask whether correlations exist between APOBEC3 expression and T cell infiltration in high-grade serous ovarian cancer (HGSOC), and assess wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 48 publications
(86 reference statements)
3
60
0
Order By: Relevance
“…In the CIN lesions, we observed A3G‐positive cells, which had a round nucleus and narrow rim of cytoplasm, infiltrating the epithelial and subepithelial stromal regions (Figure E). These A3G‐positive cells were positive for CD3, a cell marker of T lymphocytes, in accordance with previous reports in ovarian cancer (data not shown). The numbers of A3G‐positive cells infiltrating around CIN3 lesions were significantly higher than those of CIN1 and CIN2 lesions (Figure ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In the CIN lesions, we observed A3G‐positive cells, which had a round nucleus and narrow rim of cytoplasm, infiltrating the epithelial and subepithelial stromal regions (Figure E). These A3G‐positive cells were positive for CD3, a cell marker of T lymphocytes, in accordance with previous reports in ovarian cancer (data not shown). The numbers of A3G‐positive cells infiltrating around CIN3 lesions were significantly higher than those of CIN1 and CIN2 lesions (Figure ).…”
Section: Resultssupporting
confidence: 92%
“…In this study, we observed that a large number of A3G‐positive immune cells had infiltrated around the CIN lesions. Based on our preliminary study using a double‐fluorescent staining method, these cells also expressed CD3, as was reported in the case of ovarian cancers . Importantly, the number of the A3G‐positive T cells increased according to the grade of the CIN lesions, suggesting that these immune cells are involved in the pathological course of HPV‐induced CIN lesions.…”
Section: Discussionsupporting
confidence: 63%
“…As a side note, increased expression of A3D and A3H was associated with a better overall survival (OS) in this study, which seems paradoxical, or at least cannot be explained yet. Thus, further investigations concerning APOBEC expression patterns and response to checkpoint inhibitors are warranted.In high grade serous ovarian carcinomas APOBEC3 expression was significantly associated with T-cell infiltration and -seemingly paradoxically- with improved clinical outcome [69]. …”
Section: Predicting Response To Checkpoint Blockadementioning
confidence: 99%
“…In high grade serous ovarian carcinomas APOBEC3 expression was significantly associated with T-cell infiltration and -seemingly paradoxically- with improved clinical outcome [69]. …”
Section: Predicting Response To Checkpoint Blockadementioning
confidence: 99%
“…We therefore resorted to a re-analysis of publicly available single cell gene expression data. Doing so, we were able to circumvent the bias of measuring APOBEC3 activity in the tumor microenvironment (Leonard et al, 2016).…”
Section: Discussionmentioning
confidence: 99%